Evaluation and feasibility of diagnostic heatflow imaging in patients with palpable breast lesions: a pilot study - Pöschke, Patrik; Boese, Axel; Seitz, Katharina; Amann, Niklas; Eckstein, Sophie; Schulmeyer, Carla; Hack, Carolin; Heindl, Felix; Hübner, Hanna; Füller, Andreas; Fasching, Peter; Emons, Julius (Archives of Gynecology and Obstetrics, 2025)
Background: Breast cancer is the most common cancer in women, with early detection significantly improving outcomes. Heat flow imaging (HFI) is a non-invasive dynamic thermography method with prior tissue cooling. It has shown its potential as an additional diagnostic tool. The aim of the present study was to evaluate the feasibility of diagnostic HFI in patients with palpable breast lesions during outpatient visits. Methods: The patients presenting with palpable breast lesions at the Erlangen University Hospital were recruited between November 2023 and April 2024. Heat flow imaging was performed in addition to sonographic and mammographic imaging in routine care. Additionally, the patients completed a pain questionnaire to evaluate the comfort of the procedure. We used a two-phase study design. During the first phase, the imaging procedure was established and standardized. In the second phase, imaging footage was compared with conventional mammography, sonography, and histological findings. Results: Thirty-nine patients were recruited and 18 patients underwent final evaluation. Heat flow imaging successfully detected 7 out of 11 palpable carcinomas. Factors contributing to missed lesions and impairing image quality were inadequate cooling or improper camera positioning. The mean pain score reported during the procedure was 0.7 on a visual analog scale from 0 to 10, indicating minimal discomfort. Conclusions: Heat flow imaging is a feasible imaging method that may serve as a supplementary diagnostic tool for breast cancer detection in patients with palpable breast lesions. However, it is still considered an experimental method and its use should be limited in the context of clinical trials. Further research involving larger patient groups is required to validate these preliminary findings and to optimize image acquisition protocols.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Breast cancer; Heat flow imaging (HFI); Thermographic imaging